Non English Students' Attitude Towards English Language - Meinita Wahyuni; aunurrahman aunurrahman; M.Iqbal Ripo Putra; Yulia Ramadhiyanti (XXXX-XXXX, 2022)
This research aims to find out the non-English students’ attitude towards English language at IKIP PGRI Pontianak. In this research, the form of research is descriptive mixed method. The subject of the research were non-English students’ of IKIP PGRI Pontianak. The data were taken through close-ended questionnaire and unstructured interview. In analyzing the data, the interactive model of data analysis proposed by Miles and Huberman was used. The sample was selected used a quota sampling. The result of this research based on the data collected showed that the respondents tend to have positive attitude towards English language. From the results of the questionnaire on the Likert scale of 52.69%, it indicated the agree category. This value shows that the average number of non-English students agrees. Thus, it can be said that the attitudes of non-English students tend to have a positive attitude towards English. The results of the data and conclusions in this study are real results obtained from the data source itself.